WHO MARRIES WHOM MATTERS: KESAMAAN PENDIDIKAN ORANGTUA DAN BERAT BADAN SAAT LAHIR DI INDONESIA - Johanna, Mudya; Samosir, Omas Bulan (UI Scholars Hub, 2023)
Despite ongoing efforts and commitment to reducing Low Birth Weight (LBW) babies, globally, the incidence of LBW has stagnated. This study uses a combined factor of maternal and husband/partner education variables to analyze the complexity of LBW incidents. This research uses secondary data from the 2017 SDKI with a multilevel logistic regression analysis method to look at the relationship between the similarity of parental education and the baby's birth weight at the individual and community levels. The results of the research show that mothers who have husbands/partners with equivalent education and higher education (≥high school or equivalent) have a lower tendency to experience LBW than mothers who have partners with unequal education. In addition, mothers who have partners with equivalent education and low educational characteristics have a higher tendency to give birth to LBW compared to other groups of mothers. The variables, including village resident status, living in an environment or community with a high average percentage of extreme poverty, and experiencing problems related to distance to health facilities, were associated with the birth of babies with low birth weight. The importance of commitment related to education, emphasis on fulfilling the number of prenatal visits, and the intervention strategy of the Scaling Up Nutrition (SUN) Movement need to be increased to reduce the number of babies with low birth weights.